1932
DOI: 10.1002/zaac.19322040404
|View full text |Cite
|
Sign up to set email alerts
|

Zur Konstitution der ammoniakalischen Kupfersalzlösungen

Abstract: Die tiefblauen ammoniakalischen Lösungen von Kupfersalzen wurden optisch im Sichtbaren untersucht.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1932
1932
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…However, it was at the same time also noted that upon addition of a fifth equivalent of ammonia the absorption band shifts in the opposite direction, the so-called pentaammine effect . It was early shown that the rather stable (tetraammine)copper(II) complex is converted to the pentaammine complex in highly concentrated aqueous ammonia solutions. Furthermore, it was also shown that the UV−visible absorption spectrum of the copper(II) ion in the aqueous ammonia solution is but a little different from that of copper(II) in liquid ammonia . However, it was not possible from these experiments to determine whether the coordination number of five ammonia equivalents around copper(II) could be exceeded or not in a solution .…”
Section: Introductionmentioning
confidence: 99%
“…However, it was at the same time also noted that upon addition of a fifth equivalent of ammonia the absorption band shifts in the opposite direction, the so-called pentaammine effect . It was early shown that the rather stable (tetraammine)copper(II) complex is converted to the pentaammine complex in highly concentrated aqueous ammonia solutions. Furthermore, it was also shown that the UV−visible absorption spectrum of the copper(II) ion in the aqueous ammonia solution is but a little different from that of copper(II) in liquid ammonia . However, it was not possible from these experiments to determine whether the coordination number of five ammonia equivalents around copper(II) could be exceeded or not in a solution .…”
Section: Introductionmentioning
confidence: 99%
“…Cupric perchlorate forms various coordination compounds with ammonia which differ in the number of ammonia ligands or by having other ligands. The characterization of these copper perchlorate complexes and the mutual chemical transformations among them were investigated in the first third of the 20 th century [1–4]. The first copper perchlorate‐ammonia complex was probably prepared by Henry Roscoe in 1862.…”
Section: Introductionmentioning
confidence: 99%